The Relationship between Self-Motivation and Persistence in Achievement and Self-Regulated Learning Skills. A Field Study in the College of Education (Abhat Journal, 2025)
This study aims to examine the relationship between intrinsic motivation, persistence in achievement, and self-regulated learning skills among students in the five colleges of Education. The study explores the level of self-regulated learning and achievement motivation among students, and examines the relationship between the dimensions of self-regulated learning (such as planning, organization, and self-monitoring) and achievement motivation. The study results showed that students' self-regulated learning levels were above average, with variations across dimensions. The study also found that achievement motivation levels were moderately high, with variations across dimensions. A statistically significant positive relationship was found between self-regulated learning skills and achievement motivation, with all components of self-regulated learning contributing to achievement motivation, with self-motivation and discipline being the most important factors. The results also revealed statistically significant differences in self-regulated learning based on academic specialization and gender, while differences in achievement motivation were only related to academic specialization.
Keywords: Intrinsic motivation; achievement motivation; self-regulated learning; university students